Model for Evaluating the Effectiveness of Practical Training with the Use of a High-End Driving Simulator - Małgorzata Pełka; Mikołaj Kruszewski; Zbigniew Kasprzyk; Mariusz Rychlicki (Applied Sciences, 2025)
Despite the progressive development of modern technology, there is a lack of adequate and reliable training and information materials. Analyses carried out in this area show that most drivers do not have the skills to use safety systems or acquire these skills while driving. Drivers often demonstrate an incomplete understanding of them and overestimate their skills, which can jeopardize road safety. In this context, the authors of the paper set out to develop a model for evaluating the effectiveness of practical training using a high-end simulator. The research goal of the paper was to objectively measure drivers’ progress in operating safety systems after receiving practical training conducted in the AS1200-6 driving simulator located at the Motor Transport Institute. The main findings indicate that the innovative model was highly effective, with 81% of participants achieving a level rated as “acceptable” or “very good”. The model enabled more accurate and objective assessments of skills in comparison with the traditional subjective assessment of trainers, especially where driver progress was not clearly evident. The results suggest that combining the data model with trainer evaluation can be an effective evaluation mechanism in ADAS training.